Overexpression of the Potato Monosaccharide Transporter StSWEET7a Promotes Root Colonization by Symbiotic and Pathogenic Fungi by Increasing Root Sink Strength - Tamayo, Elisabeth; Figueira-Galán, David; Manck-Götzenberger, Jasmin; Requena, Natalia (Frontiers in Plant Science, 2022)
Root colonization by filamentous fungi modifies sugar partitioning in plants by increasing the sink strength. As a result, a transcriptional reprogramming of sugar transporters takes place. Here we have further advanced in the characterization of the potato SWEET sugar transporters and their regulation in response to the colonization by symbiotic and pathogenic fungi. We previously showed that root colonization by the AM fungus Rhizophagus irregularis induces a major transcriptional reprogramming of the 35 potato SWEETs, with 12 genes induced and 10 repressed. In contrast, here we show that during the early colonization phase, the necrotrophic fungus Fusarium solani only induces one SWEET transporter, StSWEET7a, while represses most of the others (25). StSWEET7a was also induced during root colonization by the hemi-biotrophic fungus Fusarium oxysporum f. sp. tuberosi. StSWEET7a which belongs to the clade II of SWEET transporters localized to the plasma membrane and transports glucose, fructose and mannose. Overexpression of StSWEET7a in potato roots increased the strength of this sink as evidenced by an increase in the expression of the cell wall-bound invertase. Concomitantly, plants expressing StSWEET7a were faster colonized by R. irregularis and by F. oxysporum f. sp. tuberosi. The increase in sink strength induced by ectopic expression of StSWEET7a in roots could be abolished by shoot excision which reverted also the increased colonization levels by the symbiotic fungus. Altogether, these results suggest that AM fungi and Fusarium spp. might induce StSWEET7a to increase the sink strength and thus this gene might represent a common susceptibility target for root colonizing fungi.